2014
DOI: 10.1128/jb.01850-14
|View full text |Cite
|
Sign up to set email alerts
|

The Diguanylate Cyclase SadC Is a Central Player in Gac/Rsm-Mediated Biofilm Formation in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative opportunistic human pathogen and a threat for immunocompromised and cystic fibrosis patients. It is responsible for acute and chronic infections and can switch between these lifestyles upon taking an informed decision involving complex regulatory networks. The RetS/LadS/Gac/Rsm network and the cyclic-di-GMP (c-di-GMP) signaling pathways are both central to this phenomenon redirecting the P. aeruginosa population toward a biofilm mode of growth, which is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 60 publications
4
94
0
3
Order By: Relevance
“…These results are similar to those described for double mutants lacking each of these DGCs in combination with removal of BifA (21). SadC is also a primary contributor to the c-di-GMP pool that promotes matrix production when the Gac/Rsm regulatory cascade is active in the P. aeruginosa strain PAK (34).…”
Section: Colony Matrix Distribution Phenotypes Suggest That Phenazinesupporting
confidence: 76%
“…These results are similar to those described for double mutants lacking each of these DGCs in combination with removal of BifA (21). SadC is also a primary contributor to the c-di-GMP pool that promotes matrix production when the Gac/Rsm regulatory cascade is active in the P. aeruginosa strain PAK (34).…”
Section: Colony Matrix Distribution Phenotypes Suggest That Phenazinesupporting
confidence: 76%
“…Through overexpression of DGC's and PDE's Moscoso et al provided evidence that the switch between type III and type VI secretion occurs as a direct result of changes in c-di-GMP metabolism. It was subsequently demonstrated that the SadC DGC is a central link between the RetS/GacS/LadS system and c-di-GMP signaling in P. aeruginosa (51). In the present study, we have added to these findings by demonstrating that c-di-GMP metabolism may change the expression of virulence factors through interference with the VfrcAMP signaling system.…”
Section: Discussionmentioning
confidence: 73%
“…The hptB gene encodes a histidine phosphotransfer protein involved in a complex regulatory cascade (47)(48)(49). The ⌬hptB mutant of P. aeruginosa PAK has been demonstrated to produce hyperbiofilms and to show elevated Pel polysaccharide production and elevated c-di-GMP levels (48,50). By mass spectrometry analysis, we found that, in the P. aeruginosa PA14 strain, the ⌬hptB mutant produces 4.3-fold more c-di-GMP than the wild type, while the ⌬bifA mutant produces 12.8-fold more c-di-GMP than the wild type.…”
Section: Resultsmentioning
confidence: 99%